2015
DOI: 10.1016/j.gerinurse.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The association between unilateral heel-rise performance with static and dynamic balance in community dwelling older adults

Abstract: INTRODUCTION As a measure of both strength and muscle endurance of the plantar flexors, the unilateral heel rise (UHR) test has been suggested as a method to evaluate balance capabilities in older adults. Thus, the purpose of this study was to examine the association between UHR performance with biomechanical measures of balance in seniors. MATERIALS AND METHODS Twenty-two older adults completed two testing sessions. The first visit included UHR performance; the second visit included dynamic and static motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…These values are inconsistent with those verified in previous studies, which indicated 25 repetitions,29,60 32–33 repetitions for the general population,51 and 17–22 for females and males,28 respectively, as cutoff values to distinguish between subjects within acceptable standards for normal strength level of PF. Few studies had identified reference values for older adults, and the results varied widely (2.7–21.3) 15,17. However, it is not possible to compare these results with that of this study accordingly, since the protocols featured the previously mentioned differences regarding the type of support (bilateral in CRS × unilateral in other studies) and movement speed (maximum possible in 30 seconds in CRS × fixed pace till exhaustion).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These values are inconsistent with those verified in previous studies, which indicated 25 repetitions,29,60 32–33 repetitions for the general population,51 and 17–22 for females and males,28 respectively, as cutoff values to distinguish between subjects within acceptable standards for normal strength level of PF. Few studies had identified reference values for older adults, and the results varied widely (2.7–21.3) 15,17. However, it is not possible to compare these results with that of this study accordingly, since the protocols featured the previously mentioned differences regarding the type of support (bilateral in CRS × unilateral in other studies) and movement speed (maximum possible in 30 seconds in CRS × fixed pace till exhaustion).…”
Section: Discussionmentioning
confidence: 78%
“…To the authors’ knowledge, there is no study that has validated CRT for assessing older adults’ performance, and the few studies targeting this population were not conducted for that purpose 15–17…”
Section: Introductionmentioning
confidence: 99%
“…Mobility is a prerequisite for the performance of most common ADLs and its maintenance is a major goal of geriatric health professionals [3]. Mobility greatly depends on the strength in the lower limbs, especially in the ankle muscles, which are particularly relevant in gait function [2,4,5] climbing stairs and rising from a chair [5][6][7]. Plantar-flexors (PF) muscles act to support and to propel the body forward in late stance and their strength is positively related to gait velocity and step length [8].…”
Section: Introductionmentioning
confidence: 99%
“…The muscle weakness of lower limbs, due to aging, is a predisposing factor for losses on postural balance 5 . Thus, the abductor and adductors muscles play an important role in maintaining pelvic stability, coordinating mediumlateral movements and maintaining postural control in narrow base 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding losses on physical function, it is unknown whether subjects with fear of falling present losses on hip muscle function, which could damage their postural balance 5,6 . Thus, the objective was to compare the isometric peak torque (PT) of hip abductor and adductor muscles among older adults with and without fear of falling.…”
Section: Introductionmentioning
confidence: 99%